Development of educational toy design attributes for cultivating social skills among preschool children - Loy, Jia Shin (2019)
Designs of educational toys play a significant role in developing the social skills of preschool children. At present, studies are limited as to how the designs of educational toys are able to contribute to these social skills, thus creating a need to determine social development attributes in educational toys design for preschool children to cultivate their social competency. The purpose of this thesis is to develop a set of educational toys design attributes in cultivating social skills of preschool children. Based on this purpose, prior investigations were carried out on methods in promoting positive social development towards young children and how they are affected by the design of educational toys. This study uses literature reviews to identify the relationship of play, educational toys and social skills towards the development of children, and subsequently showed that role play and peer interactions provided strong influences. Observations and interviews were carried out to further determine the use of role play and peer interactions in toy designs, which includes the application of triangulation technique in validity. Results of the study consists of the attributes of children’s social skills development and the relationships towards types of educational toys. These leads towards the guidelines and criteria in designing educational toys for the social skills development of preschool children. The attributes determined are allow multiplayers, shareable toys, win-lose system, allow children to express (verbally), promotes active plays and sensory trigger. The results show that these toys can serve as the platform for children to develop their social skills. Moreover, this research will serve as a guideline for parents or the public to have a deeper understanding towards the social development of children, which would nurture the growth and improve their attitude towards the children’s future success. In addition, it will also contribute towards future related research fields and benefits designers in the toy industry to have better insight when developing new toys.